Mitos dan Budaya - Mia Angeline (Humaniora, 2015)
This article describes the role of myth and some universal themes of myth, such as the creation of the world, a huge flood, death, and the end of the world. Almost all the world's myths concern this universal themes, as seen from the similarity of some of the myths followed by many cultures in the world. These myths have primary functions to human’s behavior and attitude because people keep telling almost the same myths to their predecessors. The goals for this research are (1) knowing the functions of myths with famous themes from various culture and (2) knowing the background and relationship between myths and modern culture. The result describes the relationship between the cultural myths, where the core of the story is the truth of humanity. In addition, myth acts as a template to organize their daily activities as well as human activity, but it also serves to introduce human to a greater power in the universe. The values in each story will be interpreted as rules and customs that must be met, and this has resulted in the emergence of a culture passed down from generation to generation.